2016
DOI: 10.1098/rspb.2016.1334
|View full text |Cite
|
Sign up to set email alerts
|

Diversification rates and species richness across the Tree of Life

Abstract: Species richness varies dramatically among clades across the Tree of Life, by over a million-fold in some cases (e.g. placozoans versus arthropods). Two major explanations for differences in richness among clades are the cladeage hypothesis (i.e. species-rich clades are older) and the diversification-rate hypothesis (i.e. species-rich clades diversify more rapidly, where diversification rate is the net balance of speciation and extinction over time). Here, we examine patterns of variation in diversification ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
154
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 124 publications
(185 citation statements)
references
References 50 publications
(118 reference statements)
8
154
4
Order By: Relevance
“…These rates are directly related to the current diversity of birds and mammals (Belmaker and Jetz 2015), amphibians (Pyron and Wiens 2013), and squamate reptiles (Pyron 2014). The negative effect of DR on richness is contrary to findings from previous studies Wiens 2016, Scholl and and might be explained by the occurrence of young clades with high diversification rates but with low richness (Wiens 2011). The negative effect of DR on richness is contrary to findings from previous studies Wiens 2016, Scholl and and might be explained by the occurrence of young clades with high diversification rates but with low richness (Wiens 2011).…”
Section: Discussioncontrasting
confidence: 60%
“…These rates are directly related to the current diversity of birds and mammals (Belmaker and Jetz 2015), amphibians (Pyron and Wiens 2013), and squamate reptiles (Pyron 2014). The negative effect of DR on richness is contrary to findings from previous studies Wiens 2016, Scholl and and might be explained by the occurrence of young clades with high diversification rates but with low richness (Wiens 2011). The negative effect of DR on richness is contrary to findings from previous studies Wiens 2016, Scholl and and might be explained by the occurrence of young clades with high diversification rates but with low richness (Wiens 2011).…”
Section: Discussioncontrasting
confidence: 60%
“…; Rabosky and Matute ; Gómez‐Rodríguez et al. ; Wiens ,b; Scholl and Wiens ; Cooney et al. ; Tedesco et al.…”
mentioning
confidence: 99%
“…Instead, they reported that simulations of net diversification rates often yielded significant, positive relationships between clade ages and their species richness, whereas observed relationships between clade age and richness were often nonsignificant or negative. It is unclear how these results were related to the accuracy of the MS estimators (as opposed to unrealistic simulation assumptions, see Kozak and Wiens ; Scholl and Wiens ). Similarly, these authors argued that the MS estimators should only be used when clade age and species richness are positively related (e.g., Rabosky and Matute ; Rabosky et al.…”
mentioning
confidence: 99%
“…; Jezkova and Wiens ; Moen and Wiens ). Furthermore, diversification rates of higher taxa are generally strongly related to those of the clades within them (Scholl and Wiens ). (6)R2018 acknowledged that BAMM underestimates the number of rate shifts, but defended BAMM as being “conservative.” That is, it only assigns clades different rates if there is strong support for those differences.…”
Section: Bamm Versus the Ms Estimatorsmentioning
confidence: 99%